The Influence Of Booklet On The Success Of Toilet Training In Children Aged 2-3 Years At Ra Bintang Zhafira Tulang Bawang Regency - Ranti Wulandari M; Sonda Nur Assyaidah (International Journal of Health and Pharmaceutical (IJHP), 2024)
Background: According to the Child Development Institute Toilet training, it is reported that 10 -20% of children aged 5 years, 5% of children aged 10 years, almost 2% of children aged 12-14 years, and 1% of children aged 18 years still wet the bed. Toilet training is an effort to train children to be able to control defecation (BAB) and urination (BAK) in their place (toilet). Education is one way to increase mothers' or parents' intellectual knowledge about toilet training. Education or health education can be provided using various methods and media, including: lectures, discussions, giving leaflets, booklets or direct practice related to the mother's needs. A booklet is a small book that contains writing, pictures or both. Research objective: to determine the effect of booklets on the success of toilet training in children aged 2-3 years at RA Bintang Zhafira, Tulang Bawang Regency. Research method: This research uses quantitative with a Quasy Experiment design with a one group pretest and posttest design. The population in this study was 32 mothers who had children aged 2-3 years and the sample taken was 32 respondents. The research was carried out at RA Bintang Zhafira, Tulang Bawang Regency in December 2023-January 2024. Data analysis was carried out univariate and bivariate (t test). Research results: it is known that the average success of toilet training before intervention was given to children aged 2-3 years was 8.0 and after intervention was given to children aged 2-3 years was 12.1. There is an influence of the booklet on the success of toilet training in children aged 2-3 years at RA Bintang Zhafira, Tulang Bawang Regency with p-value = 0.000 or p ≤ α (0.05). Conclusions and Suggestions: There is an influence of the booklet on the success of toilet training in children aged 2-3 years at RA Bintang Zhafira, Tulang Bawang Regency and suggestions for RA Bintang can provide health education to mothers who have toddler age children regarding the implementation of toilet training.